From isolated organization to business ecosystem. The Cocowell case - Aichner, Lara (2018)
This paper discusses and analyzes the concept of business ecosystems, including the phenomenon of value co-creation, as well as its main consequences for both a single company and the business world in general.The main objective is to understand how a company can adapt its organizational design according to an ecosystem, so that it can exchange and co-create value in a network of actors in order to accelerate innovation. Furthermore, the paper pretends to identify the main implications an ecosystem perspective has on the way business is done.The scope of the empirical research coincides mainly with the value chain of the food brand "cocowell", which involves different companies. By conducting in-depth interviews with the manufacturer and some representatives of the business partners, an analysis was carried out about the current organizational design, which at the commercial level shows some similarities to an ecosystem. In addition, the main gaps to the ideal of an ecosystem could be identified, as well as the factors that originate them and how they could be solved.